High‐Throughput Counting and Superresolution Mapping of Tetraspanins on Exosomes Using a Single‐Molecule Sensitive Flow Technique and Transistor‐like Semiconducting Polymer Dots. Issue 24 (6th May 2021) - Jiang, Yifei; Andronico, Luca A.; Jung, Seung‐Ryoung; Chen, Haobin; Fujimoto, Bryant; Vojtech, Lucia; Chiu, Daniel T.
Abstract: A method for high‐throughput counting and superresolution mapping of surface proteins on exosomes is described. The method combines a single‐molecule sensitive flow technique and an adaptive superresolution imaging method. Exosomes stained with membrane dye and dye‐conjugated antibodies were analyzed using a microfluidic platform at a flow rate of 100 exosome s −1 to determine size and protein copy number. Superresolution mapping was performed with exosomes labeled with novel transistor‐like, semiconducting polymer dots (Pdots), which exhibit spontaneous blinking with <5 nm localization error and a broad range of optical‐adjustable duty cycles. Based on the copy numbers extracted from the flow analysis, the switch‐on frequency of the Pdots were finely adjusted so that structures of hundreds of exosomes were obtained within five minutes. The high throughput and high sensitivity of this method offer clear advantages for characterization of exosomes and similar biological vesicles. Abstract : An approach is described for high‐throughput counting and superresolution mapping of surface proteins on exosomes, using a combination of a single‐molecule sensitive flow technique and an adaptive superresolution imaging method enabled by a new class of transistor‐like, photoswitching polymer dots.